First report on TTX levels of the yellow spotted pufferfish (Torquigener flavimaculosus) in the Mediterranean Sea. (15th June 2018) - Kosker, Ali Rıza; Özogul, Fatih; Durmus, Mustafa; Ucar, Yılmaz; Ayas, Deniz; Šimat, Vida; Özogul, Yeşim
Abstract: The differences of tetrodotoxin (TTX) levels in various parts of pufferfish ( Torquigener flavimaculosus ) were examined in conjunction with the seasonal and sexual variations. The TTX levels in gonads, liver, intestines, skin and muscle tissue were determined using the Q-TOF LC/MS. Instrumental analysis revealed that all examined tissues from T. flavimaculosus contained high TTX concentrations. TTX levels in the gonads, liver, intestines, skin and muscle tissue of pufferfish were within the range of 5.03–100.71, 7.04–106.80, 12.59–86.30, 33.95–139.88 and 15.88–86.07 (μg/g), respectively. It was determined that in all seasons, except for summer, female individuals had higher TTX levels than males. Among all seasons, the highest level of TTX was found in winter and the lowest in autumn. Consequently, T. flavimaculosus is a highly toxic pufferfish that is dangerous for human consumption and should not be consumed under any circumstances. Graphical abstract: Highlights: The first report is on the TTX content of T. flavimaculosus (pufferfish) in the Mediterranean Sea. TTX content in pufferfish was determined by using the Q-TOF LC/MS analysis. All seasons except for summer, female individuals had higher TTX levels than males. Regardless of gender, this species is a highly toxic pufferfish that is dangerous for human consumption.